Development of SSR markers and assessment of genetic diversity in native Nepenthes spp. in southern Thailand - Sontikun, Yaowaphan; Somwong, Benjamas; Kanjanasopa, Duangkhaetita; Thitithanakul, Suraphon; Suraninpong, Potjamarn (Ornamental Horticulture, 2025)
Nepenthes spp. (Nepenthaceae) is one of the popular genera of carnivorous plants, which has a special leaf modification with varying shapes, sizes, and shades of color. These plants exhibit high variation within species and populations, making it difficult to classify them by morphology. As a result, molecular techniques are needed to identify genetic diversity. Therefore, this study aimed to generate simple sequence repeat (SSR) markers and assess the genetic diversity of nine native Nepenthes spp. in southern Thailand. In the present study, a total of 20 SSR primer pairs containing dinucleotide or trinucleotide motifs were identified from 2,138 nucleotides and 41 ESTs of Nepenthaceae, and 950 nucleotides of carnivorous plants from that database were retrieved from GenBank. Only 10 were polymorphic, showing 2–7 alleles and, on average, 3.7 alleles per locus. Based on SSR markers, the nine Nepenthes spp. were clustered into two main groups by SSR scoring data using UPGMA cluster analysis, with a cophenetic correlation of 0.76. This is the first report that identified N. mirabilis var. globosa as distinct from N. mirabilis by SSR markers. The results suggested that SSR markers can successfully reveal variability among Nepenthes spp. They can be useful to evaluate genetic diversity studies, provide practical information for parental selection, assist breeding programs, and the result is important to the conservation action of endangered species.